Emerging functions of lycopene in the management of digestive premalignant lesions - Gan, Kerui; Shi, Wenjin; Liu, Xiangfei; Ding, Wei; Qiu, Yan; Luo, Xiaobo (Frontiers in Pharmacology, 2024)
Common digestive precancerous lesions, including oral potentially malignant disorders (OPMDs), gastric ulcers and colorectal adenoma, harbor high risk of cancerous transformation. Early intervention of these lesions is significant to prevent carcinogenesis and improve patients' prognosis. Lycopene, a carotenoid predominantly accumulated in tomatoes, is clinically recommended with its cis structure; as lycopene harbors the most potent antioxidative effects among carotenoids, its chemopreventive effects on the premalignant lesions is noted. Despite several reviews have assessed lycopene's efficacy for OPMDs, emerging studies have reported varying efficacy for digestive precancerous lesion with no comprehensive summary. Therefore, this review initially evaluates the efficacy and underlying mechanisms of lycopene for management of digestive precancerous lesions. According to the included studies, lycopene may show high promise in the management of digestive precancerous lesions, such as relieving mouth opening and burning sensation of oral submucous fibrosis (OSF), presenting potentially equivalent efficacy on managing oral lichen planus (OLP) as steroids and alleviating gastrointestinal precancers' symptoms, meanwhile lowering colon cancer risk. Moreover, its mechanisms for managing digestive precancerous lesions are concretely summarized, including antioxidative stress effects, anti-inflammatory response and regulation of cell proliferation and apoptosis, especially its modifications on TLR4/TRIF/NF-κB signaling pathway and p53-dependent cell cycle control and apoptosis. More studies are warranted to confirm its long-term efficacy and preventive role against malignant transformation of digestive precancerous lesions as evidence is insufficient.